A review of Gabonese gorillas and their pathogens: Diversity, transfer and One Health approach to avoid future outbreaks? - Boundenga, Larson; Makouloutou-Nzassi, Patrice; Ngoubangoye, Barthelemy (Frontiers in Parasitology, 2023)
In Africa, great apes, among which gorillas, are the reservoir of several infectious agents, some of which have zoonotic potential. However, scientific reports summarizing data on the pathogens harbored by some primate species still need to be published for the scientific community, conservation, and public health actors. In the case of Gabon, despite its outstanding biodiversity, particularly in great apes, and the history of outbreaks involving wildlife, there is a lack of reports on pathogens found in some ape species living in the vicinity of the human being. Thus, it is becoming urgent for us to synthesize the available data on pathogens (parasites, bacteria, and viruses) identified in gorillas living in different ecosystems of Gabon to assess the risks for the human population. Therefore, this review article presents the diversity of pathogens identified in gorillas in Gabon, their impact on primates’ health, the cases of transfer between gorillas and humans, and the interest in a One Health approach for prevention and a better understanding of the ecology of gorilla’s diseases infection in Gabon.